An experimental study on flow induced motion and energy harvesting of cylinders with different cross sections - Song, Ronglai; Xu, Peng; Jiang, Changqing; Zhang, Yuan; Li, He (Frontiers in Marine Science, 2024)
It has been known that the cross-sectional shape of a column oscillator significantly influences its vibrational characteristics and energy conversion capacity, and can alter the nature of flow-excited vibration (FIV). Whether the addition of appendages to oscillators with different cross-sectional shapes enhances energy conversion capacity remains uncertain. In this study, the vibration characteristics and energy capture capabilities of an elastically supported oscillator with a semicircular appendage, suitable for low-speed seafloor current environments, are investigated. Experiments were conducted at zero degrees incidence for Reynolds numbers ranging from 5.041 × 10³ to 7.562 × 104, resulting in turbulent wake conditions. The hydrodynamic properties of the oscillators were evaluated through statistical analysis, Proper Orthogonal Decomposition (POD), and vortex core identification of Particle Image Velocimetry (PIV) fields. The energy capture capability of the oscillator was assessed through statistical analysis of its vibration displacement, frequency, and amplitude. The study's results indicate that an oscillator with symmetric sharp attachments and without vortex reattachment is favorable for galloping with self-excitation. Under equivalent conditions, the Circular-T-shaped oscillator demonstrates superior energy conversion capacity compared to existing models, with the galloping branch being the most efficient for energy conversion; the peak efficiency is 24.5% (Ur = 14.5). This study provides some baseline data and optimization solutions for flow-induced motion power generation.